Association of Per3 length polymorphism with bipolar I disorder and schizophrenia - Karthikeyan, Ramanujam (2014)
BACKGROUND: Sleep-wake disturbances have frequently been reported in bipolar disorder and schizophrenia, and are considered to be caused by an underlying circadian rhythm disorder. The study presented here was designed to investigate the existence of Per3 polymorphism in bipolar disorder type I (BD-I) and schizophrenic patients in South India. METHODS: Blood samples were collected from 311 BD-I patients, 293 schizophrenia patients, and 346 age- and sex-matched normal controls. Per3 genotyping was performed on DNA by polymerase chain reaction using specific primers. RESULTS: An increased prevalence of five repeat homozygotes was seen in BD-I patients as compared with healthy controls (odds ratio =1.72 [95% confidence interval: 1.08-2.76, P=0.02]). In BD-I patients, the frequency of the five repeat allele was higher (allele frequency =0.41), and that of the four repeat allele lower (allele frequency =0.36) (χ (2)=4.634; P<0.03) than in the control group. No significant association was observed in the allele frequencies of four and five repeat alleles in schizophrenia patients when compared with controls. CONCLUSION: The occurrence of the five repeat allele of Per3 may be a risk factor for BD-I onset in this ethnic group.